Welfare State differences in Selected European Union Countries under Conditions of Uncertainty - Aldona Migała-Warchol*; Vitas, Arturas; Dalia Prusaitiene; Maciej Warchoł; Olga Buckiūnienė (Annals of Mathematics and Physics, 2025)
Abstract The article discusses the welfare state models developed for some European Union countries in situations of uncertainty, such as economic crises, the COVID-19 pandemic, and growing social inequalities. The research explores Goal 8 of United Nations Agenda 2030 for Sustainable Development: to ensure that economic growth is continuous, inclusive, and durable; and labor is productive, secure, and decent, available to all. The analysis has also brought out the imperative of attaining an inclusive economy within the frame of modern global challenges, including unemployment, inequality, and environmental sustainability. It further emphasizes the inter-relationship between technological changes, global trade patterns, and shifts in labor market conditions, requiring all-inclusive policies that would grant opportunities even to the marginal groups like women, youth, and people with disability. The publication is an attempt at undertaking an analysis of the following indicators related to Goal 8 of Agenda 2030: Decent Work and Economic Growth. Indicators of this goal include the following: gross domestic product per capita, share of GDP, employment rate for women, long-term unemployment rate, young people neither in employment nor in education and training, and fatal accidents at work. The models were to be prepared using data from the Eurostat databases for the years 2008-2023 in selected countries within the EU: Lithuania, Poland, Germany, Sweden, and Luxembourg. To do this, it was necessary to apply descriptive statistical methods, primarily the method of linear regression and trend function. This study explores the balancing act pursued by countries to combine economic productivity with environmental responsibility, while the growth strategies are aligned in coherence with the circular economy and green transformation principles. Research identifies policy frameworks that effectively include decent work standards, protection of workers' rights, and lifelong learning and skill development. In the final instance, the publication underscores the fact that solving structural inequalities, adapting to changes in technology, and economic development towards the inclusive and sustainable future of all until 2030 is the coordinated effort of international responsibility. At the end, parameters of trend function were estimated for chosen indicators, what made possible verification of the research hypotheses considered as true by us.